Development of Kerteh port towards a national petrochemical hub port in Malaysia - Jagan Jeevan (Fakulti Maritim dan Sains Marin, 2011)
Malaysia is one of the main countries in the world which produces oil, natural gas and manufacturing petrochemical products. Thus, the port which specializes in petrochemical production plays a major role in petrochemical industry development. Kerteh Port in Terengganu, Gebeng in Kuantan, Tanjung Langsat in Johor and Bintulu Port in Sarawak are four major ports involved in petrochemical industry. Among these ports, Kerteh has a great potential to become the National Petrochemical Hub Port which attributes to five main factors such as geographical factors, government incentives, safety procedure, hightech facilities and professionalism in human resource.